Resting and daily energy expenditures during reproduction are adjusted in opposite directions in free‐living birds. (2nd September 2014) - Welcker, Jorg; Speakman, John R.; Elliott, Kyle H.; Hatch, Scott A.; Kitaysky, Alexander S.
Summary: Reproduction is energetically expensive, and daily energy expenditure (DEE) often peaks during the period of rearing young. The 'potentiation' hypothesis predicts that high DEE needs to be sustained by a corresponding up‐regulation of metabolic machinery; thus, a concomitant increase in the resting metabolic rate (RMR) is expected. Alternatively, the 'compensation' hypothesis predicts that DEE and RMR are regulated independently and animals may maintain low RMR to maximize the energy available for reproduction. This might particularly be the case if DEE was limited, for example, by extrinsic food supply or intrinsic physiological factors. We tested these hypotheses in free‐living seabirds by manipulating their energy demands (experimentally reduced or increased brood size) and supplies (providing supplemental food), and simultaneously measuring their DEE and RMR (by the doubly labelled water method and an indirect hormonal proxy, respectively). In support of the 'compensation' hypothesis, metabolic rates were adjusted independently and in opposite directions with an increase in DEE and a decrease in the hormonal proxy for RMR in individuals rearing young compared to birds with removed broods. Energy expenditure of unfed birds with chicks appeared to be limited as experimental brood enlargement did not cause an increase in DEE. Supplemental feeding did not allow DEE to exceed this apparent limitation. We propose that a reduction in the resting metabolism is a strategy to increase allocation of energy to reproduction when DEE is constrained and that this constraint is unlikely to be related to food supply. Abstract : Lay Summary